“Universal test and treat” program reduced TB incidence by 75% among a cohort of adults taking antiretroviral therapy (ART) in Gurage zone, South Ethiopia - Tadele Girum (Tropical Diseases, Travel Medicine and Vaccines, 2020)
Abstract Background Tuberculosis (TB) remains the leading cause of morbidity and mortality in peoples living with HIV and at least 25% of deaths are attributed to TB. Many countries implement the Universal Test and Treat (UTT) program for HIV, which is believed to reduce the incidence of TB. However, there are limited studies that evaluate the impact of UTT on TB incidence. Therefore, by recruiting a cohort of ART users in the “UTT” and “differed treatment” programs, we aim to measure the effect of the UTT program on TB incidence. Objective To measure the effect of “UTT” program on TB incidence among a cohort of adults taking antiretroviral therapy (ART) in Gurage Zone, South Ethiopia. Methods A retrospective cohort study was conducted through record review over 5 years (2014–2019) in public health facilities in Gurage Zone. Three hundred eighty-four records were randomly selected and reviewed using a standardized structured checklist. Data was entered using Epi Info™ Version 7 and analyzed by STATA. A generalized linear model with binomial link function was fitted to measure the adjusted incidence density/incidence rate ratio and to identify predictors of incidence difference between the two programs. Results During the follow up period, 39 incident TB cases were identified with an overall incidence rate of 4.79/100 person-year (PY). TB incidence was significantly lower in the UTT cohort (IR = 2.10/100 PY) in comparison to the differed program cohort (IR = 6.23/100 PY). The adjusted incidence rate ratio (AIRR) of TB among patients enrolled in the UTT program was; 0.25 (95% CI = 0.08–0.70). Thus, there was a reduction of TB incidence by 75% in the UTT program compared to differed program. In addition, IPT (isoniazid preventive therapy) use (AIRR = 0.35 (95% CI = 0.22–0.48)), WHO Stage I and II (AIRR = 0.70 (95% CI = 0.61–0.94)) and higher base line CD4 count (AIRR = 0.96 (95% CI = .94–0.99)) significantly reduced the incidence of TB. However, treatment failure increase the incidence (AIRR = 5.8 (95% CI = 1.93–8.46)). Conclusion TB incidence was significantly reduced by 75% after UTT. Therefore, intervention to further reduce the incidence has to focus on strengthening UTT program and IPT.